(untitled) (Actual Problems of Psychology in Educational Institutions, 2019)
The article presents the characteristics of the character accentuation of the personality of modern Ukrainian adolescents. The author investigates the role of characterological features, in particular character accentuation, in the process of personal formation of adolescents. Analyzes the major classifications of accentuations by H. Schmieschek. The importance of character accentuations in the predictor structure of students’ frustration response profiles is revealed. Testing of students of middle classes, namely adolescence. The obtained data identified the types of character accentuations, which are students. Also, with the help of testing, it is established what type of character accentuation is the most common among modern adolescents.